PENGARUH METODE PLYOMETRIC TERHADAP KEMAMPUAN VERTICAL JUMP PADA SISWA EKSTRAKURIKULER BOLA VOLI DI SMKN 1 KAYONG UTARA - Pardik, Pardik; Supriatna, Eka; Hidasari, Fitriana Puspa (Universitas Tanjungpura, 2022)
AbstractPardik (2021) The Effect of Plyometric Methods on Vertical Jump Women in Volleyball Extracurricular Students at SMKN 1 Kayong Utara (Supervisor I: Eka Supriatna M.Pd and Advisor II: Fitriana Puspa Hidasari M.Or). The problem in this study is the vertical jump ability of volleyball players at SMKN 1 Kayong Utara, who take volleyball extracurricular activities is still categorized as lacking and the plyometrix method has not been applied. The purpose of this study was